(untitled) (Journal of Plant Disease Sciences, 2020)
Five newer and commercially available fungicides were evaluated during five Rabi seasons of Rabi 2012-13, Rabi 2013-14, Rabi 2014-15, Rabi 2015-16 and Rabi 2016-17 against neck blast disease (Pyricularia oryzae) of rice at Rice Research Station, Moncompu, Alleppey District, Kerala. The treatments were kresoxym methy l44.3 SC, tebuconazole 50% + trifloxystrobin 25% 75 WG, tebuconazole 250 SC, carbendazim 50WP with the standard check fungicide iprofenphos48 EC. The confirmative farm trials were conducted at six locations of Kuttanad region during Rabi 2017-18. The new generation fungicide molecule kresoxym methyl 44.3SC@ 1ml/liter water was found most promising fungicide in restrict the neck blast disease (7.84 %) and gave the maximum grain yield (7373 kg/ha) and followed by tebuconazole 250 SC @ 1.5 ml/liter water(8.87 % and 7168 kg/ha), respectively.